Non-stationary model of the solar core - Skoromnaya, S.F.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2020)
The main parameters of the standard model of the Sun are considered, according to which the Sun is considered as a spherically symmetric and quasistatic star, and thermonuclear reactions of the pp-cycle mainly occur inside it and the energy is uniformly released at a rate of 2·10⁻⁴J/(kg·s). Based on observational data it was concluded that the Sun is not a star with uniformly ongoing processes, it is characterized by oscillatory processes and flashes. It is proposed to consider the non-stationary model of the Sun, in which it is required to take into account the existence of electromagnetic waves in the plasma of the solar core and, as a result, the existence of wave collapses (WC). A three-dimensional axially symmetric WC is considered and an estimate of the velocity of removal of the plasma of the solar core during the development of a three-dimensional axially symmetric WC is given. For the considered WC the existence of three directions of flows of elementary plasma volumes relative to the observer is demonstrated: one direction is due to the moving the elementary plasma volume from the observer and the other - to him. The third direction of moving of the elementary plasma volumes is perpendicular to the direction of observation and their velocity relative to the observer is zero. It is concluded that the existence of such motions of elementary plasma volumes during the development of WC can leave a definite imprint on the parameters of the synthesis products in them. Розглянуто основні параметри стандартної моделі Сонця, згідно з якою Сонце розглядається як сферичносиметрична і квазістатична зірка, а всередині неї протікають переважно термоядерні реакції рр-циклу, і відбувається рівномірне виділення енергії зі швидкістю E = 2·10⁻⁴Дж/(кг·с). Виходячи iз спостережних даних, зроблено висновок про те, що Сонце не є зіркою з рівномірно поточними процесами, йому притаманні коливальні процеси і спалахи. Запропоновано розглядати нестаціонарну модель Сонця, в якій необхідно враховувати існування електромагнітних хвиль в плазмі ядра Сонця і, як наслідок, існування хвильових колапсів (ХК). Розглянуто тривимірний аксіально-симетричний ХК, і дана оцінка швидкості виносу плазми ядра Сонця при розвитку тривимірного аксіально-симетричного ХК. Для розглянутого ХК показано існування трьох напрямків потоків елементарних обсягів плазми відносно спостерігача: один напрямок обумовлено рухом елементарного обсягу плазми від спостерігача, інший - до нього. Третій напрям руху елементарних обсягів плазми здійснюється перпендикулярно напрямку спостереження, і швидкість їх рухів відносно спостерігача дорівнює нулю. Зроблено висновок про те, що існування таких рухів елементарних обсягів плазми при розвитку ХК може накладати певний відбиток на параметри продуктів синтезу в них. Рассмотрены основные параметры стандартной модели Солнца, согласно которой Солнце рассматривается как сферически-симметричная и квазистатическая звезда, а внутри нее в основном протекают термоядерные реакции рр-цикла, и происходит равномерное выделение энергии со скоростью E = 2·10⁻⁴Дж/(кг·с). Исходя из наблюдательных данных, сделан вывод о том, что Солнце не является звездой с равномерно текущими процессами, ему присущи колебательные процессы и вспышки. Предложено рассматривать нестационарную модель Солнца, в которой необходимо учитывать существование электромагнитных волн в плазме ядра Солнца и, как следствие, существование волновых коллапсов (ВК). Рассмотрен трехмерный аксиально-симметричный ВК, и дана оценка скорости выноса плазмы ядра Солнца при развитии трехмерного аксиально-симметричного ВК. Для рассмотренного ВК показано существование трех направлений потоков элементарных объемов плазмы относительно наблюдателя: одно направление обусловлено движением элементарного объема плазмы от наблюдателя, другое - к нему. Третье направление движения элементарных объемов плазмы осуществляется перпендикулярно направлению наблюдения, и скорость их движения относительно наблюдателя равна нулю. Сделан вывод о том, что существование таких движений элементарных объемов плазмы при развитии ВК может накладывать определенный отпечаток на параметры продуктов синтеза в них.